Occupational asthma in an electronics factory: a case control study to evaluate aetiological factors. Issue 3 (June 1979) - Burge, P Sherwood; Perks, W H; O'Brien, I M; Burge, A; Hawkins, R; Brown, D; Green, M
Abstract : This is the final part of a study carried out to investigate occupational asthma due to sensitivity to colophony fumes (a component of soldering flux) in an electronics factory. Fifty-eight workers with occupational asthma employed on the main shop floor were investigated. In them the interval between first exposure and sensitisation varied widely with a group becoming sensitive within one to two years of first exposure, and another group whose sensitisation was delayed for three to 23 years. Once sensitised the interval between arriving at work and the onset of daily symptoms seemed to be bimodally distributed, resembling the immediate and late asthmatic symptoms seen on provocation testing. Twenty-three out of 58 had no definite daily deterioration at work but improved at the weekends. Wheeze and breathlessness occurred in the evenings at home in most, and one-third were woken by breathlessness at least on some nights. These 58 cases were compared with 48 controls without occupational asthma who had worked on the same shop floor for at least four years. Mean levels of FEV1 were significantly worse in the cases before exposure on Monday morning. The cases also had more than twice as much sickness absence as controls. FEV1 fell by more than 10% over a working shift in 33% of cases and 5% of controls. Atopy (a positive skin prick test to one or more common allergens) and a past history of allergic disease were weakly but significantly associated with being a case. The effects of smoking and a family history of allergic disease were trivial. Prick testing with an antigen derived from the colophony in the solder flux was completely negative, but cases and controls had significantly raised levels of total IgM compared with blood bank controls, perhaps suggesting some previously unrecognised immunological process.